Speech Processing Using FD Independent Component Analysis Algorithm - N. Shanmuga Priya, Dr. (International Journal of Engineering and Technology, 2018)
Speech is most mighty and usual medium to alternate the information amongst individuals. The speech method additionally goes underneath the system of some application tools to reward the know-how in effective approach. Audio supply separation is the crisis of computerized separation of audio sources gift in a room, making use of a set of differently placed microphones, shooting the auditory scene. On this paper, proposed a novel quick Frequency domain ICA algorithm using two viable implementations. Additionally, a effective possibility Ratio soar approach to the permutation difficulty of ordering sources along the frequency axis is provided. The suggestion of exploiting the additional geometrical expertise, such because the microphone spacing, so as to participate in permutation alignment using beam forming is then examined and ultimately discussed accuracy, sensitivity and Throughput ration values are evaluate with current and proposed ways.Â Â Â
Keywords: frequency domain; speech processing; independent component analysis.